Amplified North Atlantic warming in the late Pliocene by changes in Arctic gateways. Issue 2 (20th January 2017) - Otto‐Bliesner, Bette L.; Jahn, Alexandra; Feng, Ran; Brady, Esther C.; Hu, Aixue; Löfverström, Marcus
Abstract: Under previous reconstructions of late Pliocene boundary conditions, climate models have failed to reproduce the warm sea surface temperatures reconstructed in the North Atlantic. Using a reconstruction of mid‐Piacenzian paleogeography that has the Bering Strait and Canadian Arctic Archipelago Straits closed, however, improves the simulation of the proxy‐indicated warm sea surface temperatures in the North Atlantic in the Community Climate System Model. We find that the closure of these small Arctic gateways strengthens the Atlantic Meridional Overturning Circulation, by inhibiting freshwater transport from the Pacific to the Arctic Ocean and from the Arctic Ocean to the Labrador Sea, leading to warmer sea surface temperatures in the North Atlantic. This indicates that the state of the Arctic gateways may influence the sensitivity of the North Atlantic climate in complex ways, and better understanding of the state of these Arctic gateways for past time periods is needed. Key Points: Closure of Arctic gateways in a new reconstruction of mid‐Piacenzian paleogeography reduces simulated Arctic freshwater exports to the North Atlantic and enhances the AMOC Simulated regional patterns of temperature show better correspondence with proxy‐indicated warm sea surface temperatures in the North Atlantic The climatic response to the closure of Arctic gateways is not a linear combination to the closure of the individual straits